2014
DOI: 10.1002/pola.27497
|View full text |Cite
|
Sign up to set email alerts
|

Efficient solvent‐free alternating copolymerization of CO2 with 1, 2‐epoxydodecane and terpolymerization with styrene oxide via heterogeneous catalysis

Abstract: The alternating copolymerization of CO2 with the terminated epoxides anchoring long alkyl groups is rarely reported because of their low reactivity and polycarbonate selectivity. This work describes a well‐controlled solvent‐free copolymerization of CO2 with 1, 2‐epoxydodecane (EDD) with a long electron‐donating alkyl group via the catalysis of Zn‐Co(III) double metal cyanide complex catalyst. The productivity of the catalyst was up to 2406 g polymer/g Zn, that is, EDD conversion was 99.2%. The alternating deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…12 Importantly, it is also possible to regulate T g of the CO 2 /epoxide copolymer via Zn−Co(III) DMCC catalysis by tuning the reaction temperature and CO 2 pressure. 29,52 For copolymers with side branched alkyl and aryl groups, the T g s increased from 35 to 84°C with increasing steric hindrance (i.e., carbon numbers C2, C4, and C6 to C7) of the substituent groups. This could effectively inhibit the free rotation of the backbone.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…12 Importantly, it is also possible to regulate T g of the CO 2 /epoxide copolymer via Zn−Co(III) DMCC catalysis by tuning the reaction temperature and CO 2 pressure. 29,52 For copolymers with side branched alkyl and aryl groups, the T g s increased from 35 to 84°C with increasing steric hindrance (i.e., carbon numbers C2, C4, and C6 to C7) of the substituent groups. This could effectively inhibit the free rotation of the backbone.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…14,16,28,29 Recently, a nanolamellar Zn−Co(III) DMCC was observed to effectively catalyze the alternating copolymerization of CO 2 with epoxides with long side alkyl groups. 30 These results led us to systematically study the substituent effects of the epoxides on the alternating copolymerization of CO 2 /epoxide using this catalyst.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Moreover, the copolymer with 70.7% carbonate content presents high thermal decomposition temperature of 250 o C and relatively high T g of 31.2 o C. Although we observed that Zn-Co(III) DMCC was a regioselective catalyst for ROP of epichlorohydrin on the site of methine group [142], we had no direct evidence for supporting the regioselective CO 2 /epichlorohydrin copolymerization. Terpolymerization of two epoxides with CO 2 could also performed well by Zn-Co(III) DMCC catalyst, affording terpolymers with tunable T g s [143]. The terpolymerization of CO 2 , styrene oxide and 1, 2-epoxydodecane with electron-donating dodecane group was successfully performed by using Zn-Co(III) DMCC catalyst, resulting in a new random terpolymer with single T g s in a wide range of 3 to 56 o C.…”
Section: Structural Effect Of Epoxides On Co 2 /Epoxide Copolymerizationmentioning
confidence: 96%
“…However, Zhang and co‐workers showed that also aliphatic polycarbonates with a flexible backbone may exhibit T g s up to 84 °C depending on their side chains. While the T g decreases with increasing alkyl length to −38 °C, the glass transition may increase up to 84 °C by steric influences . Also long alkyl side chains with up to 20 carbon atoms were already incorporated in aliphatic polycarbonates to tune the thermal properties .…”
Section: Functional Ethylene‐oxide‐based and Terminal Epoxide Monomersmentioning
confidence: 99%
“…Using a binary or bifunctional Co(III)‐based catalyst system, the incorporation of PO resulted in a random terpolymerization and the incorporation of CHO in an alternating terpolymerization with more than 99% carbonate linkages . In addition, Fan and co‐workers introduced random terpolymers obtained from styrene oxide, 1,2‐epoxydodecane, and CO 2 with T g s in a range of 3–56 °C depending on the comonomer ratio …”
Section: Functional Ethylene‐oxide‐based and Terminal Epoxide Monomersmentioning
confidence: 99%